The Immunotherapeutic Effect of SIRPα-Silenced DCs against Cervical Cancer - Xiaojie Li; Wenying Zhou; Yanlan Liang; Changzhi Xu; Zhizhi Xie; Jiayin Liang; Bo Hu (Journal of Immunology Research)
Signal regulatory protein α (SIRPα), a transmembrane protein that is predominantly expressed in dendritic cells (DCs) or macrophages, interacts with CD47 that is overexpressed in almost all types of tumor cells. The interaction between SIRPα and CD47 leads to a negative signal that prevents the phenotypic and functional maturation of DC and inhibits phagocytosis. The SIRPα knockdown in DCs that were pulsed with a modified HPV16E7 (HPV16mE7) protein with enhanced antigenicity and reduced transformation activity results in increased cytokine (TNF-α/IL-12/IL-6) secretion, IFN-γ secretion by T lymphocytes, and in vitro/in vivo tumoricidal activity against cervical cancer cells. Taken together, these results suggest that SIRPα-silenced DC vaccination presented potential therapeutic implications against cervical cancer.